Hospital-Related Lineage of USA300 Methicillin-Resistant Staphylococcus aureus (MRSA) to Cause Bacteremia in Iran. (15th April 2023) - Navidinia, Masoumeh; Zamani, Samira; Mohammadi, Anis; Araghi, Shahram; Amini, Chakameh; Pourhossein, Behzad; Goudarzi, Mehdi
Abstract : Staphylococcus aureus is an important pathogen that causes bloodstream infections. This study is aimed at assessing the genotypic characteristics of S. aureus strains responsible for bloodstream infections. An epidemiological study was conducted using 85 S. aureus strains isolated from bloodstream infections. Susceptibility was tested using the broth microdilution method and disk diffusion. All detected methicillin-resistant S. aureus (MRSA) isolates were confirmed by mecA PCR assays. S. aureus isolated from bacteremia were characterized using SCCmec, spa, and multilocus sequence typing methods. The prevalence of S. aureus strains responsible for bloodstream infections was 38.8%. All isolates were MRSA. Multidrug resistance (MDR) was present in 84.7% of isolates. MRSA isolated categorized within six clonal complexes including CC8 (60%), CC22 (22.4%), CC5 (5.9%), CC30 (4.7%), CC45 (4.7%), and CC59 (2.3%). The main lineages found were USA300/CC8-MRSA-IV/t008 (41.2%), followed by ST22-SCC mec IV/t790 (9.4%), ST239-SCC mec III/t037 (7.1%), ST22-SCC mec IV/t032 (7.1%), ST239-SCC mec III/t631 (5.9%), ST239-SCC mec III/t860 (5.9%), ST22-SCC mec IV/t852 (5.9%), ST5-SCC mec IV/t002 (4.7%), ST45-SCC mec IV/t038 (4.7%), ST30-SCC mec IV/t318 (4.7%), ST59-SCC mec IV/t437 (2.3%), and ST225-SCC mec II/t045 (1.1%). Resistance to vancomycin amounted to 5.9% of isolates that belonged to ST239-SCC mec III/t037 (80%) and ST8-SCC mec IV/t008 (20%). The emergence of USA300 strains in bloodstream infections in our country is a serious alarm and highlights the significant invasion of this lineage into the healthcare system. MDR patterns among these strains appear to be becoming the biggest problem in healthcare treatment.